Persepsi Kesiapan Alat Keselamatan: Studi Kasus KM Sabuk Nusantara 96 Berdasarkan Solas Chapter III - Reinhard, Eugenne Gladwin; Anggraeny, Kuncowati; Kristiawan, Deddy (CV Insan Kreasi Media, 2025)
The perception of safety equipment readiness refers to the crew’s assessment of the condition, availability, and functionality of safety equipment on board, as well as their confidence that such equipment is reliable and ready to be used in emergency situations. This perception encompasses physical aspects, such as completeness and operational feasibility of the equipment, as well as psychological aspects, namely the crew’s confidence in the effectiveness of the equipment based on their experience, training, and understanding of SOLAS Chapter III procedures. This study aims to examine the perception of the crew of KM Sabuk Nusantara 96 regarding the safety equipment regulated under SOLAS Chapter III and to analyze their preparedness in responding to emergency situations. This qualitative research employs semi-structured interviews, observation, and document analysis involving six crew members with different roles. The findings indicate a generally positive perception of equipment completeness; however, variations in understanding and practical experience are evident among the crew. Senior crew members demonstrate a strong grasp of emergency procedures, while newer crew members require further training. The implementation of SOLAS Chapter III on this vessel faces operational challenges, including logistical constraints and limited access to training in remote areas. The study recommends the enhancement of intensive and scheduled training programs, improved access to maritime safety training, the development of monitoring and evaluation systems, and the strengthening of safety culture on board. These findings provide important implications for the development of maritime safety policies for Indonesia’s pioneer vessels.